School education reforms and development of a new Soviet school space in Kazan during the 1920s and 1930s - A.A. Salnikova; D.S. Zhuravlev (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article examines the role of the school education reforms enacted in the 1920s–1930s for promoting the formation of a new Soviet school space. The focus is on the school space of Kazan, a major pre-revolutionary and Soviet provincial center with the long-inherited educational traditions reconsidered during the first decades of the Soviet regime. The research is based on the documents from the collections of the State Archives of the Republic of Tatarstan, which have been for the first time introduced into the scientific use. The results obtained show that the school space of Kazan underwent an overhaul when the Soviet power had established itself. This was a direct consequence of the reforms and innovations aimed to build a radically new school for the Soviet people. The school reforms also influenced the Soviet urban planning practices by gradually putting a greater emphasis on the needs of the Soviet school, intensifying the school construction, and expanding the network of model schools in connection with the “unification” of the Soviet educational process. The conclusion is that the Kazan case generally fits into the key educational and urban development processes that were taking place in the Soviet territory of that time.